BEHAVIOURAL STUDIES OF EXTERNAL ATTRIBUTES OF BREAD AND PASTRY IN SLOVAK REPUBLIC - Mária Holienčinová; Ľudmila Nagyová; Ingrida Sedliaková (Polityki Europejskie, Finanse i Marketing)
The aim of the research was to determine Slovak consumer's behaviour when purchasing and consuming bread and pastry. As a research method, was used a structured questionnaire consisting of 16 questions. The total number of respondents was 350 randomly selected respondents, from which were analyzed the answers of 291 respondents consuming bread and pastry. For a deeper analysis of the obtained results, there were set out assumptions, which have been tested with the use of Pearson's chi-square test and Cramer's contingency coefficient. As the results of the research show, the mostly preferred filling of pastries is the curd, jam and poppy filling, the preferred taste of salty bread is the crackling, corn and cheese taste, 61 % of respondents are in many cases in their purchase of bread and pastry influenced by the smell of fresh bread, 52 % of respondents need to catch the bread or pastry before their purchase, 44 % of respondents sometimes take in account the sound, which the bread makes when they are catching it, 53 % of respondents prefer the cake with more colours.